Reverse Radial Forearm Flap Versus Retrograde Ulnar Dorsal Artery Flap for Soft Tissue Reconstruction of Dorsal Hand Defects - Rashid, Sobia; Zulfiqar, Bushra; Sheikh, Unza; Gulzar, Sadaf; ali khan, Faisal akhlaq; Sami, Waqas (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To restore the soft tissue in dorsal hand defects, this study compares the functional consequences of a retrograde ulnar dorsal arterial flap against a reverse radial forearm flap. Method: In the Civil Hospital Karachi's Centre for Plastic and Reconstructive Surgery, we performed a prospective comparison study. Including 37 individuals in each group, the desired sample size was 74. Patients of either gender who suffered trauma to the dorsum of their hands and wrists between the ages of 20 and 50, either from RTA, mechanical trauma, work-related incidents, or weapon injuries, fulfilled the inclusion criteria. SPSS version 22.0 will be applied to enter the data and evaluation. When it involves quantitative factors like age, time since injury, defect size, and DASH score, the mean as well as the standard deviation will be determined. A t-test will be utilized for contrasting the DASH grades in each group; a p-value of ≤0.05 is considered significant. Result: Forty nine 49(66.2%) of those enrolled in the current research were male and based on the mean the age was 56.2±5.3. Of the individuals who participated, 53(71.6%) suffered from diabetes, and 66(89.15%) had hypertension. There were a total of 32(43.2%) patients with moderate wounds. Flap necrosis afflicted 12(32.4%) of those undergoing treatment in group A versus 26(70.3%) of the individuals in group B. 12(32.4%) of the individuals who participated in group B plus 21(56.8%) of those patients in group A similarly had graft survival. Practical implications: Our study shows that all the methods are equally fine and it depends on the surgeon’s decision to go with whichever the surgeon wishes. The RRFF provides versatile coverage for larger defects, while RUDA preserves the radial artery, potentially preferable for smaller ones. Further randomized controlled trials are needed. Conclusion: We concluded that both methods are fine based on the situation, and no technique is better than the other one. The RRFF provides versatile coverage for larger defects, while RUDA preserves the radial artery, potentially preferable for smaller ones. Further randomized controlled trials are needed